2011
DOI: 10.1371/journal.pone.0017919
|View full text |Cite
|
Sign up to set email alerts
|

The Seroprevalence of Pandemic Influenza H1N1 (2009) Virus in China

Abstract: BackgroundMainland China experienced pandemic influenza H1N1 (2009) virus (pH1N1) with peak activity during November-December 2009. To understand the geographic extent, risk factors, and attack rate of pH1N1 infection in China we conducted a nationwide serological survey to determine the prevalence of antibodies to pH1N1.Methodology/Principal FindingsStored serum samples (n = 2,379) collected during 2006-2008 were used to estimate baseline serum reactogenicity to pH1N1. In January 2010, we used a multistage-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
42
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 20 publications
12
42
2
Order By: Relevance
“…Individuals of all professions, except for teachers, had significantly lower OR of A(H1N1)pdm09 seropositivity than children in family care; this was discordant with the report of Xu et al (12). In addition, the symptoms (cold, fever, and cough) were not significantly associated with the seropositive rate.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Individuals of all professions, except for teachers, had significantly lower OR of A(H1N1)pdm09 seropositivity than children in family care; this was discordant with the report of Xu et al (12). In addition, the symptoms (cold, fever, and cough) were not significantly associated with the seropositive rate.…”
Section: Discussionsupporting
confidence: 58%
“…We did not have baseline (pre-pandemic) data for accurately inferring the attack rates among the population in Shandong Province. However, the baseline serum samples collected from individuals in China prior to May 2009 had shown a very low positive rate (1.2z) against A(H1N1)pdm09 (12). Third, the HI assay may not be the most sensitive assay for detecting low levels of A(H1N1)pdm09 (e.g., when compared to microneutralization); thus, we may have underestimated seropositivity in the serological survey samples.…”
Section: Discussionmentioning
confidence: 97%
“…Under method 1 for estimating the number of symptomatic A(H7N9) virus infections, nationwide serosurvey and ILI surveillance of A(H1N1)pdm09 in China during June 2009 to January 2010 indicated that around 0.75% of symptomatic A(H1N1)pdm09 virus infections sought medical care at ILI sentinels. 23 Assuming that a similar proportion of symptomatic A(H7N9) virus infections attended ILI sentinels, we estimated that approximately 3,020 (95% credible interval, CrI: 900–7,800) and 5,310 (95% CrI: 880–17,300) symptomatic A(H7N9) virus infections had occurred in Shanghai and Nanjing, respectively (Appendix). With 40 hospitalised cases occurring in Shanghai and Nanjing, pro-rata extrapolation based on 123 total hospitalisations to date gives a total of 27,000 (95% CrI: 9,530–65,000) symptomatic A(H7N9) virus infections.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely both susceptibility and reporting rates were higher in children and lower in adults, but the exact age-dependence of each is difficult to resolve without additional data. Post-pandemic serology data now available from a number of countries [49, 50, 51, 52] shows age-specific seroconversion rates more compatible with estimates from the Baseline model than from the other two models (which produce much higher infection attack rate estimates in adults), suggesting that variation in susceptibility to infection with the H1N1pdm virus was more extreme than suggested from serological testing of pre-pandemic samples.…”
Section: Discussionmentioning
confidence: 95%